Information seeking behavior of Padjadjaran University marine science students within the framework of the Anomalous State of Knowledge theory - Shelpi Nur Awaliyah; Adinda Nuur Hasanah; Faisa Fahrul Rozi; Prijana Prijana (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. The information seeking behavior of Marine Science students is important in broadening understanding of a multidisciplinary field and is prone to triggering knowledge gaps. Anomalous State of Knowledge (ASK) theory is relevant to explain these conditions, because it views information seeking as a response to anomalies in individual knowledge structures. This study aims to identify whether the information seeking behavior of Marine Science students is dynamic, with the formulation of the problem: whether studying topics relevant to marine microbiology is significantly associated with interest in seeking information outside the field. Research Methods. This research method uses survey method, with a simple random sampling method. Data Analysis. Data were analyzed using the Pearson product-moment correlation test using SPSS software. Results. The results showed a significant relationship between engagement in marine microbiology topics and interest in cross-disciplinary information exploration, reflecting an active response to knowledge anomalies. Students not only filled information gaps but also developed broad and adaptive search strategies. Conclusion. This research shows that Marine Science students' information-seeking behavior is dynamic and aligned with the ASK principle, so this approach is important for understanding and developing academic information systems responsive to evolving information needs.